PENGARUH SISTEM BIROKRASI, FASILITAS DAN PEMENUHAN KONSEP SYARIAH TERHADAP KEPUASAN PENGGUNA PADA KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH BMT TUMANG BOYOLALI - Parli, Parli; Trisnowati, Juni; Budiwanarto, Kim (Universitas Of Surakarta, 2020)
The purpose of this study was to find out: 1) the influence of the bureaucratic system on service user satisfaction, 2) the effect of facilities on service user satisfaction, 3) the effect of fulfilling sharia concepts on service user satisfaction, 4) the influence of the bureaucratic system , facilities and fulfillment of sharia concepts to service users' satisfaction. This study included quantitative descriptive research whose conclusions were obtained based on the results of statistical analysis with the object of research at KSPPS BMT Tumang Boyolali. A sample of 161 people from a population of 300 people with incidental sampling techniques. Instruments used with questionnaires and data analysis techniques used are multiple linear regression analysis, t test, F test, R2 test. Regression analysis results obtained regression equation: Y = 3.223 + 0.249 X1 + 0.255 X2 + 0.298 X3, which means that service user satisfaction is influenced by the bureaucratic system, facilities provided and fulfillment of sharia concepts (compliance). Based on the analysis and discussion it can be concluded that: 1) the bureaucratic system influences the satisfaction of service users. (2) facilities affect the satisfaction of service users. (3) fulfillment of sharia concepts affects the satisfaction of service users. (4) the bureaucratic system, facilities and fulfillment of the concept of sharia together affect the satisfaction of service users. (4) bureaucratic system, facilities provided and fulfillment of sharia concepts affect the satisfaction of service users by 59.5%, while the remaining 40.5% is influenced by other variables outside of this study